CoVim : converting Vim into a real-time collaborative editor - Saumya Mohan. (2012)
With the advance of globalization and information technology, there has been great emphasis on teamwork and collaboration across the globe. Today, geographic locations are no longer barriers to collaboration across distance but it is the unavailability of collaborative applications and platforms that serves as the bottleneck for real time collaboration. As a result, tremendous efforts have been made to provide collaboration capabilities in single-user applications.